Africanization in British Multinationals in Ghana and Nigeria, 1945–1970. Issue 4 (6th February 2019) - Decker, Stephanie
Abstract : Multinationals experienced significant legitimacy challenges in less-developed countries between 1945 and 1970. Corporate responses to these challenges cover three distinct periods. Unsuccessful postwar attempts focusing on colonial welfare concerns were followed by pragmatic endeavors intended to repair corporate reputations by Africanizing senior management. By the 1960s, this had become a common approach to legitimization. The challenges of Africanizing ethnocentric multinationals led to organizational changes: internationally diversified multinationals were better able to decentralize subsidiary management, while the late 1960s saw regionally focused multinationals absorbed by more diversified multinationals. Organizational survival was directly linked to legitimacy advantages derived from Africanization.